Clinical genetic testing in pediatric cardiomyopathy: Is bigger better?. Issue 1 (3rd August 2017) - Ouellette, A.C.; Mathew, J.; Manickaraj, A.K.; Manase, G.; Zahavich, L.; Wilson, J.; George, K.; Benson, L.; Bowdin, S.; Mital, S.
Abstract : Background: For clinical genetic testing of cardiomyopathy (CMP), current guidelines do not address which gene panels to use: targeted panels specific to a CMP phenotype or expanded (panCMP) panels that include genes associated with multiple phenotypic subtypes. Aim: Our objective was to assess the clinical utility of targeted versus panCMP panel testing in pediatric CMPs. Methods: 151 pediatric patients with primary hypertrophic ( n = 66), dilated ( n = 64), restrictive ( n = 8), or left‐ventricular non‐compaction ( n = 13) CMP who underwent clinical genetic panel testing at a single centre were included. PanCMP ( n = 47) and targeted panel testing ( n = 104) were compared for yield of pathogenic variants and variants of unknown significance (VUS). Results: Pathogenic variants were identified in 26% of patients, 42% had indeterminate results (only VUS detected), and 32% had negative results. Yield was lower (15%) in panCMP vs. targeted panel testing (32%) ( P = .03) in all CMP subtypes. VUS detection was higher with panCMP (87%) than targeted panel testing (30%) ( P <.0001). PanCMP panel testing only identified pathogenic variants in genes that overlapped targeted panels. Conclusion: PanCMP testing did not increase diagnostic yield compared to targeted panel testing. Until accuracy of variant interpretation with panCMP panels improves, targeted panels may be suitable for clinical testing in pediatric CMP. Abstract :